Childless by circumstance – Using an online survey to explore the experiences of childless women who had wanted children. (March 2021) - Chauhan, Dilan; Jackson, Emily; Harper, Joyce C
Abstract: Childlessness is increasing globally. This study aimed to explore the experiences of childless women who had wanted children. An online survey study was promoted through social media to recruit women aged ≥46 years who were childless by circumstance. The survey remained open for 15 days. In total, 303 survey responses were collected, 176 of which were complete surveys. In total, 15.3% (27/176) of women who had wanted children reported that they had not tried to have children, most commonly due to the lack of a partner (40.7%, 11/27). Of the 139 women who had tried to have children, 70.5% (98/139) had used calendar-based menstrual cycle tracking methods to identify their fertile window, and many had undergone fertility checks including hormone tests (75.5%, 105/139) and ultrasound scans (71.2%, 99/139). A significant proportion of women had experienced a miscarriage (40.2%, 56/139). Many women had decided not to have any fertility treatment (43.2%, 60/139). For those who did, the majority had tried in-vitro fertilization (74.6%, 59/79). The most common reason that women gave for stopping fertility treatment was due to emotional reasons (74.7%, 59/79). When asked how women felt now about their childlessness, the most common issues identified were unhappiness (85/158, 54%), acceptance (43/158, 27%) and happiness (30/158, 19%). There should be more support for unsuccessful fertility patients and other childless women, and more emphasis should be placed upon fertility education in order to ensure that women are better informed about fertility issues.